Homomorphic self-incompatibility, with stylar rejection site, in Luehea grandiflora Mart. and Zucc. (Tiliaceae-Malvaceae s.l.) - Gibbs, P. E.; Oliveira, P. E.; Ranga, N. T. (Georg Thieme Verlag Kg, 2003)
The breeding system of Luehea grandiflora (Tiliaceae-Malvaceae s.l.) was investigated using hand pollinations and fluorescence microscopy studies of pollen tube growth. Although selfed flowers persisted for some 10 days, our study indicates that L. grandiflora is self-incompatible, with self pollen tube inhibition in the upper style, as occurs in many taxa with homomorphic, gametophytic self-incompatibility (GSI). L. grandiflora is only the second species reported within the Malvales with homomorphic stylar inhibition. This result is discussed within the context of a report for self-compatibility in this species, and we also consider the phylogenetic implications for the occurrence of GSI in the family Malvaceae s.l.
Keywords: Malvales; Luehea; breeding system; self-incompatibility; homomorphic gametophytic self-incompatibility; late-acting self-incompatibility